Variability of maize yield and some soil properties in an exhaustively cultivated field in the School of Agriculture, Ikorodu - A. S., Fasina (Universiti Putra Malaysia Press, 2002)
The variability of maize yield and some soil properties in an exhaustively cultivated field in the School of Agriculture, Ikorodu was examined using a coefficient of variation and stepwise multiple regression analysis for two years (1990 and 1991). The variability of individual soil properties and maize yield as indicated by cv values differed widely. Soil chemical properties (ex, Ca, Mg, Ex, Avail. P and zinc) varied more than the physical properties of the soil (sand and water holding capacity). Variability of some soil properties and maize yield were likely to have been markedly influenced by previous land use and other management practices around the exhaustively cultivated field. In 1990, 18 soil properties explained 92.51 % of the variation in the yield of maize on the exhaustively cultivated field. Compared to 87.29% in 1991, each of the soil properties exerted a different influence on the yield of maize. Soil properties which exerted stronger influences on the yield of maize within the cultivated field were available P, Exchangeable Potassium, organic matter, water holding capacity, Exchangeable calcium, sand and zinc. This study has highlighted the tremendous amount of soil and maize yield variability that may exist within a small exhaustively cultivated field. The approach used in this study seems reasonable for improving crap yield on the field. It would be useful for selecting different soil praperties for land and soil fertility evaluation studies.